Survey, Identification and Management of Major Diseases of Latkan in Some Selected Areas of Bangladesh (Bangladesh Journal of Agricultural Research, 2023)
Latkan (Baccaurea sp.), an underutilized minor fruit has drawn popularity because of its nutritional value in Bangladesh. Its cultivation, therefore, is gaining momentum . So, a survey on the health status and prevalence of diseases on Latkan was carried out at Shibpur upazilla of Narsingdi and Valuka upazilla of Mymensingh district during the cropping season 2019-2020. Growers of Latkan in the two Upazillas were interviewed to know about the occurrence of diseases of latkan and their management. Infected leaves, twigs and fruits were collected, and the pathogens were isolated and identified in the Plant Pathology Laboratory of BARI, Gazipur. Three diseases were identified viz. (i) gray leaf blight caused by Pestalotiopsis sp., (ii) die-back caused by Diplodia sp. and (iii) anthracnose caused by Colletotrichum sp. The prevalence of the diseases varied for location, age of the orchards and type of the disease. Anthracnose predominated in the old orchards compare to gray leaf blight and die-back. Field experiment was conducted for chemical management of anthracnose indicated that Tilt (Propiconazole @ 0.5ml/L) and Autostin (Carbendazim @ 1g/L) were effective measures to control the disease.Bangladesh J. Agril. Res. 47(2): 215-223, June 2022